Theatrical Performance and Aesthetic Communication in Darkest Night Directed by Festus Dairo - Ojo, Abayomi C.; Olatunji, Olalekan F. (SCHOLARS: Journal of Arts & Humanities, 2023)
The theatre functions as a platform for communication; however, the surge in audiences' level of media literacy and aesthetic taste caused by the exposure to media elements has warranted a review of the medium of communication to include a critical use of aesthetics in performance. Therefore, directors like Festus Dairo have identified the use of special effects make-up and mixed-media as currencies for creating contemporary performances with an aesthetic essence. This paper engages Ole Thyssen’s aesthetic communication theory as a theoretical framework as it examines Dairo’s art of aesthetic communication using special effects make-up and mixed-media techniques. It is a descriptive study that secured its data through participatory observation of the 2023 production of Darkest Night by the Zion Royal Theatre. As Dairo seeks to create an aesthetic theatre experience capable of sustaining audience attention through visual elements and media technology, he uses special effects of make-up to create mental images emanating from the visual adornment of characters through the use of special effects of make-up and a deliberate use of media elements which include pre-recorded dialogues and sound amplification; music; interactive lights and audio subtitling in connection with the ongoing live action. Hence, the use of special effects make-up and mixed-media techniques in the performance under study proves to be a viable method of aesthetic communication capable of enhancing interpretation, creating a robust theatre experience, and sustaining the overall contemporary theatre-going culture.